Decreased T530-pSIRT1 Expression in CD45- Cells After Red Grape Administration - Agustin Iskandar; Carla Pramudita Susanto; Chilmi S; Wihastuti TA (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
T530-pSIRT1 is one of the biomarkers that shows senescence activity. CD45- cells are the phenotype for late Endothelial Progenitor Cells (EPCs) expressing endothelial antigens. Resveratrol in red grapes is thought to be able to increase T530-pSIRT1 expression and improve endothelial quality. This study aimed to determine the change in T530-pSIRT1 expression by CD45- cells after the administration of red grapes. This study had a quasi-experimental pre-test-post-test one-group design. Research subjects were taken using consecutive sampling methods in the adult population aged 45-55 years. Expression of T530-pSIRT1 was analyzed from the number of CD45- cells and Mean Fluorescence Index (MFI) of CD45- cells using the immune flow cytometry method. Statistical analysis used GraphPad version 9.2.0. The number of research subjects was 17 people with a mean age of 47.3 years and 52.9% were female. There was a significant decrease in the number of CD45- cells (p=0.02) and a significant decrease in T530-pSIRT1 expression indicated by MFI CD45- cells, which were significant (p = < 0.0001). Decrease in T530-pSIRT1 expression in CD45- cells is thought to be caused by several factors that cannot be controlled during the study subject's consumption of red grapes such as diet, exercise, mental stress, and rest periods. Further research is needed to determine the appropriate dose and timing of red grape consumption to increase SIRT1 levels. Consumption of red grapes decreased expression of T530-pSIRT1, which could be caused by the dose and time of consumption of red grapes and the lifestyle of the research subjects that could not be controlled.